1999
DOI: 10.1007/s007010050391
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Cerebral Plasticity by Intra-Operative Neurophysiological Monitoring: Report of an Uncommon Case

Abstract: It has been postulated long ago that "eloquent" areas shift their location in patients with arteriovenous malformations (AVM). Obviously the "motor region" in not located in the precentral gyrus in a patient with an AVM in the "motor region". We report on the case of a 15-year old boy with an AVM in the left sensorimotor cortex, in whom intra-operative mapping showed an inexcitability of the precentral gyrus, while stimulation of the cortex anterior to the primary motor cortex elicited motor responses. This in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The present study confirmed earlier animal experiments [5861] and human studies [14, 39, 6264], which indicated that corticospinal connections are not limited to the primary motor cortex but extend to different regions of the sensorimotor system. Approximately half of the primate brain's pyramidal tract neurons are located in postcentral areas, for example, the primary somatosensory cortex, sharing functional properties with regard to movement-related activity and discharge patterns as a function of muscle strength with precentral pyramidal tract neurons [31, 6567].…”
Section: Discussionsupporting
confidence: 92%
“…The present study confirmed earlier animal experiments [5861] and human studies [14, 39, 6264], which indicated that corticospinal connections are not limited to the primary motor cortex but extend to different regions of the sensorimotor system. Approximately half of the primate brain's pyramidal tract neurons are located in postcentral areas, for example, the primary somatosensory cortex, sharing functional properties with regard to movement-related activity and discharge patterns as a function of muscle strength with precentral pyramidal tract neurons [31, 6567].…”
Section: Discussionsupporting
confidence: 92%
“…Although reorganization of the motor cortex [13] and plasticity characterized by abnormal branching of the CSTs [14] have previously been reported, this study is to our knowledge the first description of the functional reorganization of an existing tract to serve as a CST in children.…”
Section: Reorganization Of the Corticospinal Tract Scantlebury Et Al 57mentioning
confidence: 92%